Experimental analysis of the modal characteristics of rail fastening clips. (February 2020) - Sun, Linlin; Yan, Ziquan; Xiao, Junheng; Fang, Hangwei; Cui, Shukun
It is usually difficult to obtain the modal characteristics of the rail fastening clip analytically owing to its complex spatial structure and operating environments. Therefore, experimental modal testing is frequently adopted to identify the modal characteristics of rail fastening clips. This study takes the SKL 15 clip of the Vossloh 300-1 fastening system as the research object to analyse the following three aspects in great detail: (1) Locations of the measurement points are reasonably designed to capture all modes of the clip in the frequency range 0–1000 Hz. (2) The appropriate sensors are selected for the clip in different operating situations by comparing the measured results of three kinds of sensors, namely the accelerometer, laser vibrometer and sound pressure sensor. In addition, the test results suggest that the accelerometer which has a strong anti-disturbance ability in an ambient environment is recommended to be chosen in a noisy environment while the laser vibrometer and sound pressure sensor which have no added mass to the tested structures may be used in an indoor environment with suitable temperature and low noise. (3) In order to eliminate the effect of the additional mass on the modal characteristics of the clip, the accelerometer is recommended to be installed at the rear end of the side leg of the clips in the experimental modal test.